New Type of sub-THz Oscillator and Amplifier Systems Based on Helical-Type Gyro-TWTs - Marek, Alexander (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2023)
This work presents the development of a new sub-THz source for the generation of trains of coherent high-power ultra-short pulses at 263 GHz via passive mode-locking of two coupled helical gyro-TWTs. For the first time, it is shown that the operation of such passive mode-locked helical gyro-TWTs in the hard excitation regime is of particular importance to reach the optimal coherency of the generated pulses. This could be of particular interest for some new time-domain DNP-NMR methods.